Targeted mass spectrometry for monitoring of neural differentiation - Sucha, Rita; Kubickova, Martina; Cervenka, Jakub; Hruska-Plochan, Marian; Bohaciakova, Dasa; Vodickova Kepkova, Katerina; Novakova, Tereza; Budkova, Katerina; Susor, Andrej; Marsala, Martin; Motlik, Jan; Kovarova, Hana; et al. (Biology open, 2021)
Human multipotent neural stem cells could effectively be used for the treatment of a variety of neurological disorders. However, a defining signature of neural stem cell lines that would be expandable, non-tumorigenic, and differentiate into desirable neuronal/glial phenotype after in vivo grafting is not yet defined. Employing a mass spectrometry approach, based on selected reaction monitoring, we tested a panel of well-described culture conditions, and measured levels of protein markers routinely used to probe neural differentiation, i.e. POU5F1 (OCT4), SOX2, NES, DCX, TUBB3, MAP2, S100B, GFAP, GALC, and OLIG1. Our multiplexed assay enabled us to simultaneously identify the presence of pluripotent, multipotent, and lineage-committed neural cells, thus representing a powerful tool to optimize novel and highly specific propagation and differentiation protocols. The multiplexing capacity of this method permits the addition of other newly identified cell type-specific markers to further increase the specificity and quantitative accuracy in detecting targeted cell populations. Such an expandable assay may gain the advantage over traditional antibody-based assays, and represents a method of choice for quality control of neural stem cell lines intended for clinical use.
Keywords: Cell Line; biologické markery; Neural differentiation; vývojová regulace genové exprese; Biomarkers; Cell Lineage; Gene Expression Regulation, Developmental; Cell line characterization; buněčná diferenciace; Selected reaction monitoring; imunohistochemie; Mass Spectrometry; neurony; stanovení celkové genové exprese; buněčný rodokmen; Gene Expression Profiling; lidé; Neural Stem Cells; Immunohistochemistry; Humans; Neurons; Protein marker; Mass spectrometry; neuroglie; buněčné linie; Neuroglia; hmotnostní spektrometrie; nervové kmenové buňky; Neural stem cell; Cell Differentiation